مفهوم القيادة الإدارية من منظور الفكر الإداري المعاصر والشريعة الإسلامية: The Concept of Administrative Leadership from the Perspectives of Modern Management Thought and Islamic Sharī’ah - Ben Zara, Yusef Muhrm; Abdul Muthaliff, Mohamed Mihlar (‘Abqari Journal, 2019)
This study discusses the concept of administrative leadership in the Western theories and Islamic law. There are many studies in the contemporary management thought that approves Islamic law in the importance of administrative leadership and its role in nation-building and communities, but these studies differed from Islamic law in terms of the concept of administrative leadership. This difference may have a negative effect on those who play a role of leadership, and thus will be reflected in the public and private stakeholders at all levels, whether of government or private nature. Therefore this study singled out the concept of administrative leadership from the perspective of modern management thought and Islamic law and made a comparative study between them with a view stand at the position of Islamic law these concepts espoused by thinkers and researchers in the modern management thought based on Western theories. The study concludes with the recommendations and findings which urge taking action under the Divine Knowledge from the Holy Qurān and the Sunnah of the Prophet in the Muslims’ lives, even administrative leadership. In addition, it motivates the knowledge of other civilizations that help in the development and progress of the Ummah, and does not contradict with Islamic values and ethics. Keywords: administrative leadership, modern management thought, Islamic Sharī’ah. ملخص تتناول هذه الدراسة مفهوم القيادة الإدارية في الفكر الإداري المعاصر والشريعة الإسلامية، وحيث أن هناك العديد من الدراسات في الفكر الإداري المعاصر التي توافق الشريعة الإسلامية في أهمية القيادة الإدارية ودورها في بناء الدول والمجتمعات، إلا أن هذه الدراسات اختلفت مع الشريعة الإسلامية من حيث المفهوم، وهذا الاختلاف قد يكون له التأثير السلبي على من يقوم بهذا بالدور، وبالتالي سينعكس على المصلحة العامة والخاصة في جميع الأصعدة سواءً كانت ذات الطابع الحكومي أو الخاص، ولذلك اختصت هذه الدراسة بمفهوم القيادة الإدارية من منظور الفكر الإداري المعاصر والشريعة الإسلامية، ولتحقيق مقاصد البحث اتَّبعت الدراسة المنهج الاستقرائي التأصيلي النقدي وذلك بقصد الوقوف عند موقف الشريعة الإسلامية من هذه المفاهيم التي يتبناها المفكرون والباحثون في الفكر الإداري المعاصر المبنية على النظريات الغربية، وتختم الدراسة بالنتائج التي من أهمها؛ تعارض المفاهيم والنظريات الغربية مع كثيراً من أحكام الشريعة الإسلامية، القيادة الإدارية في الإسلام لها مفهوم شمولي لا ينطوي فقط على مصالح الدنيا فحسب بل يشمل المصالح الدينية والدنيوية، تكون رؤية القيادة الإدارية في الإسلام وفق رؤية شرعية بخلاف رؤية القيادة الإدارية في الفكر الإداري المعاصر فهي تكون وفق تطلعات وهوى القائد الشخصية. الكلمات المفتاحية: القيادة الإدارية، الفكر الإداري المعاصر، الشريعة الإسلامية